2001
DOI: 10.1159/000050897
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β Affects Retinal Pigment Epithelial Cell Proliferation via Protein Kinase C Pathways

Abstract: Background: The aim of this study is to see the effect of interferon β (IFN-β) on cell proliferation and the protein kinase C (PKC) signaling pathway. Methods: Proliferation of cultured human retinal pigment epithelium (RPE) cells, with various concentrations of IFN-β, and with or without 3% fetal calf serum (FCS), was assessed by cell counting. Effects of short (3 h) or prolonged (48 h) exposure of RPE cells to natural human IFN-β were assessed by 3H-thymidine uptake. Cytosolic and membranous PKC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The utility of IFN-β was found to be more promising as it promotes proliferation and repair of damaged RPE and regression of CNV in monkey AMD models. More studies on the effectiveness of IFN-β have been published in literature [38][39][40][41]. Taken together, these studies indicate the importance of IFNs in AMD pathogenesis.…”
Section: Is Ifn-γ a Possible Target For Treatment Of Amd?mentioning
confidence: 94%
“…The utility of IFN-β was found to be more promising as it promotes proliferation and repair of damaged RPE and regression of CNV in monkey AMD models. More studies on the effectiveness of IFN-β have been published in literature [38][39][40][41]. Taken together, these studies indicate the importance of IFNs in AMD pathogenesis.…”
Section: Is Ifn-γ a Possible Target For Treatment Of Amd?mentioning
confidence: 94%
“…In contrast, PKC-␦ has been proposed to have predominantly proapoptotic actions, as it is cleaved and activated by caspase 3 (21)(22)(23)(24). In addition, PKC has been implicated in mediating the actions of type 1 IFN in other cell systems (32), and PKC-␦ has been identified as the serine kinase responsible for type 1 IFN-mediated phosphorylation of STAT1 (33). The possible involvement of PKC isoenzymes was determined initially by assessing the translocation of PKC isoenzymes to the cell membrane fraction, which is an indicator of enzyme activation.…”
Section: Alternative Pi3k Targets Are Activated By Ifn-␤mentioning
confidence: 99%
“…5 Protein kinase C (PKC) is a multigene family of phospholipid-dependent serine-threonine kinases that mediates the phosphorylation of numerous protein substrates in signal transduction and plays a central role in cellular processes such as proliferation, differentiation, mitosis, and inflammatory reaction. 6,7 It has been well documented that the PKC family is involved in the processes of proliferation, migration, phagocytosis, and gel contraction in RPE cells, [8][9][10][11][12][13][14] which are all reportedly implicated in the pathogenesis of PVR. We have also found that hypericin, a specific inhibitor of PKC, has potential as a therapeutic drug for PVR through its inhibition of the Ca 2+ influx pathway.…”
Section: Introductionmentioning
confidence: 99%